Pengaruh Literasi Keuangan, Sikap Keuangan, Kemampuan Akademik, Gender, Pengelolaan Uang Saku, dan Pendidikan Keluarga Terhadap Perilaku Pengelolaan Keuangan - Zaky Syahputra; Rangga Putra Ananto; Elfitri Santi (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to examine the influence of financial literacy, financial attitudes, academic ability, gender, pocket money management, and family education on the financial management behavior of accounting students at Politeknik Negeri Padang. This is a quantitative study conducted on students from the Accounting Department of Politeknik Negeri Padang from the 2020, 2021, 2022, and 2023 cohorts who reside in Limau Manis Subdistrict, Pauh District, Padang City, West Sumatra. The research was carried out starting in July 2024 until completion. The sampling technique used in this study was non-probability sampling. The results of the study indicate that financial attitudes, pocket money management, and family education have a significant influence on students' financial management behavior. Meanwhile, financial literacy, academic ability, and gender do not have a significant effect on the financial management behavior of accounting students at Politeknik Negeri Padang.